Benediction [large type] - Haruf, Kent (Center Point Large Print, 2013)
When Dad Lewis is diagnosed with terminal cancer, he and his wife work together to make his final days comfortable. Their daughter, Lorraine, comes home from Denver to help look after Dad, which helps to soften the bitter absence of the Lewis's estranged son, Frank. Next door, young Alice lives with her grandmother, and Dad's condition stirs painful memories of her own mother's death. Meanwhile, the town's newly arrived preacher attempts to mend his strained relationships with his wife and teenaged son, a task that proves all the more challenging when he faces the disdain of his congregation after offering more than they are accustomed to getting on a Sunday morning. And throughout, an elderly widow and her middle-aged daughter do everything they can to ease the pain their friends and neighbors are suffering. Bracing, sad and deeply illuminating, Benediction captures the fullness of life by representing every stage of it -- including its extinction -- as well as the hopes and dreams that sustain us along the way.